(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
The present article deals with the so called concession concept, a unit of thought representing pieces of knowledge on the universal relations existing in the outer and inner world, its significant features forming concession as a type of the concept. Abundance of linguistic expressive means of concession lets us interpret it from the angle of linguistic field theory.